Better protected, better paid: evidence on how employment protection affects wages - Karen van der Wiel (Institute for the Study of Labor (IZA), 2009)
This paper empirically establishes the effect of the employer's term of notice on the wage level of employees. The term of notice is defined as the period an employer has to notify workers in advance of their upcoming dismissal. The wages paid during this period are an important element of firing costs and hence employment protection. To find a causal effect, I exploit the exogenous change in the term of notice that resulted from the introduction of a new Dutch law in 1999. Strong evidence is found that a longer 'dormant' term of notice leads to higher wages. In my sample, an additional month of notice increases wages by three percent, ceteris paribus.
urn:nbn:de:101:1-200910141465
Keywords: C23; J31; J38; J63; 330; Employment protection; term of notice; wages; Lohnniveau; Kündigungsschutz; Reform; Wirkungsanalyse; Lohn; Niederlande